SOME APPROACHES TO DEVELOPING FUTURE ENGINEERS’ MORALITY WHEN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Saienko, N.; Саенко, Н. В.; Саєнко, Н. В. (Харьковский национальный автомобильно-дорожный университет, 2017)
The role of moral education in technical university students’ training is considered. The reasons of enhanced interest to parables as a means of ethic development in the present day reality are revealed. The key components of the process of teaching morality through foreign language are substantiated.
НЕКОТОРЫЕ ПОДХОДЫ К ВОСПИТАНИЮ МОРАЛЬНОСТИ БУДУЩИХ ИНЖЕНЕРОВ В ПРОЦЕССЕ ПРЕПОДАВАНИЯ АНГЛИЙСКОГО ЯЗЫКА
ДЕЯКІ ПІДХОДИ ДО ВИХОВАННЯ МОРАЛЬНОСТІ МАЙБУТНІХ ІНЖЕНЕРІВ У ПРОЦЕСІ ВИКЛАДАННЯ АНГЛІЙСЬКОЇ МОВИ
Keywords: morality; technical university students; parables; methods; foreign language; моральность; студенты технического вуза; иносказания; методы; иностранный язык; моральність; студенти технічного ВНЗ; іносказання; методи; іноземна мова; 378.147